Analisis Metode Bermain Peran Terhadap Perkembangan Sosial – Emosional Anak Usia 4-5 Tahun - Safana, Vinka Alza; Retnoningsih, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Abstract The role-playing method is an effective approach in supporting the social emotional development of children aged 4-5 years. This research uses the SWOT analysis method, which includes identifying strengths, weaknesses, opportunities, and threats. Strengths of the role-playing method include increasing children's creativity, self confidence, empathy and social skills. However, weaknesses include time requirements and potential lack of focus on the activity. Opportunities that can be utilized include application in various learning contexts and collaboration with parents, while possible threats include negative influences from the environment and lack of support from caregivers. The results of this analysis suggest that the role play method is not only beneficial in developing children's social skills, but also as a means to build positive interpersonal relationships. This research is expected to provide insights for educators and parents in implementing the roleplaying method more effectively. Keyword: Social-Emotional, Role Play, Early Childhood